The Roles of a Multidrug-Resistant Klebsiella pneumoniae High-Risk Clone and Its Resistance Plasmids on the Gastrointestinal Colonization and Host-Defense Effectors in the Gut - Balazs Stercz; Judit Domokos; Zsuzsanna A. Dunai; Nora Makra; Janos Juhasz; Eszter Ostorhazi; Bela Kocsis; Dora Szabo (MDPI AG, 2024)
The asymptomatic gastrointestinal colonization of multidrug-resistant (MDR) bacteria can lead to difficult-to-treat infections. We investigated the role of host factors influencing colonization in an orogastrical murine infection model using a CTX-M-15- and OXA-162-producing Klebsiella pneumoniae ST15 (MDR-KP) strain, as well as Escherichia coli J53 (EC) and E. coli transconjugants with an IncFII(K) plasmid carrying CTX-M-15 (EC-CTXM), and with an IncL plasmid carrying OXA-162 (EC-OXA) genes. The fecal bacterial count in colony-forming unit/gram stool (CFU/g) was determined by cultivation, IgA and defensin levels by ELISA, and gut microbiota by 16S rRNA analysis. The CFU was the lowest in EC, followed by EC-OXA and EC-CTXM, and the highest in the MDR-KP group. The IgA level in feces increased in MDR-KP, EC-CTXM, and EC-OXA, and did not change in EC. The beta-defensin 3 level markedly increased in all groups, with the highest values in MDR-KP and EC-CTXM. Alpha-defensin-5 increased in all groups especially in EC. In microbiota, the Bacteroidota phylum was dominant in MDR-KP, EC-CTXM, and EC-OXA, whereas Proteobacteria was dominant in EC. The Muribaculaceae family was significantly more common in the MDR-KP and EC-OXA groups, while the Lachnospiraceae family was dominant in the EC group. While fecal IgA levels positively correlated with colonizing bacterial CFU, the alpha-defensin 5 levels inversely correlated with CFUs and IgA levels. The presence of the IncFII(K) plasmid induced beta-defensin 3 production. The amounts of the Muribaculaceae family members exhibited a correlation with the IncL plasmid. The detected amounts of the Lachnospiraceae family indicated the protective role against the high-risk clone and the resistance plasmids' dissemination. Our results suggest that not only the MDR-KP clone itself but also the resistance plasmids play a primary role in the colonization rate in the gastrointestinal tract. Both the MDR-KP clone as well as the IncFII(K) and IncL resistance plasmids provide survival and colonization benefits in the gut.